Mechanical properties of structural adhesives enhanced with natural date palm tree fibers: Effects of length, density and fiber type. (1st April 2020) - Khakpour, H.; Ayatollahi, M.R.; Akhavan-Safar, A.; da Silva, L.F.M.
Abstract: Recently, the importance of environmental issues has made scholars to focus on the implementation of bio-degradable resources in different applications. The same trend is being followed in adhesives improvement by adding different bio friendly materials. In this study, the possibility of implementation of natural resources obtained from annual pruning of date palm tree is investigated by considering the effects of fiber treatment, fiber length and fiber density on the mechanical properties of structural adhesives in an empirical way using a considerable amount of experimental work. In this journey, first the tensile strength of different types of fibers, in raw and treated conditions is compared and the morphology of fibers surface is examined. Then, the effects of type, length, weight ratio and treatment conditions on the tensile strength improvement of different adhesives are investigated. The results demonstrate the success of implementation of the aforementioned bio friendly fibers in this application. In some cases, the increase in strength even exceeds 64%. Moreover, a higher fiber length results in higher increase in strength while the strengthening effect diminishes as the fiber weight ratio surpasses a certain value. Using scanning electron microscope technique, the effect of treatment on fiber surfaces is also analyzed.